MEMBANDINGKAN ALGORITMA D’SATUR DENGAN ALGORITMA VERTEX MERGE DALAM PEWARNAAN GRAF TAK BERARAH - Daratun Nasihin; Endang Lily; M. D. H. Gamal (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article provides an undirected graph vertex coloring. Graph vertex coloring can be done by using the coloring algorithm, including d’satur algorithm and vertex merge algorithm. Of the two algorithms, a more efficient algorithm is determined that generates chromatic number χ(G) which is the minimum or produces fewercolors. This article is a review of the work of Handrizal et. al [Journal of Computer Science 7(5):664-670].